A Study of Unethical Practices in the Construction Industry and Potential Preventive Measures - Shah, R K; Alotaibi, M (Journal of Advanced College of Engineering and Management, 2018)
The conflict of interest amongst the professionals like client and contractor project managers, site engineers, quantity surveyors and designers/architects play crucial roles for the unethical practices and consequently these practices have adverse impact on the product quality, faith of clients and investors’ confidence in the construction industry. Hence, this research is aimed at examining the common forms of unethical practices among professionals in the construction industry as well as uncovering the factors that have encouraged these practices. This study depends on the questionnaire survey amongst professionals of the construction industry. The survey is conducted to recognise the view of key stakeholders from different perspectives of the affected parties on the concept of business ethics in the building and construction industry, which has key contribution on the national economic growth of the developing countries. The survey concludes that untimely legal action including changing project manager’s responsibility and delays in payment processes are key ethical practices from owner/client aspect, while contractor’s unethical practices are under bidding, bid cutting and shopping, bid rigging and over billing. But from the consultant aspect; lack of supervision, poor monitoring and taking bribes under different pretend are found to be the encouraging factors for unethical conducts in the construction industry. It is also found that accepting the bribes, gifts and conflicts of interest are the most common forms of unethical practices. The findings from the study are expected to help as an important eye opener to policy makers and regulatory agencies in detecting and preventing unethical practices. In conclusion, avoiding the conflict of interest and promoting the ethic codes to professionals will help to restore the investor and people confidence, faith of the clients and improve the quality of buildings and infrastructures. The study recommends that promoting awareness regarding the values of ethical behaviour at different forum and ensuring the effective punishment for unethical activities at different stages of project life cycle might reduce the unethical practices in the construction industry. Journal of Advanced College of Engineering and Management, Vol. 3, 2017, Page: 55-77